2016
DOI: 10.1136/bmjopen-2015-008571
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a multicentre nasopharyngeal carcinoma awareness programme in Indonesia

Abstract: Objective To evaluate the effectiveness of a nasopharyngeal carcinoma (NPC) awareness programme on the short-term and long-term improvement of knowledge and referral of patients with NPC by primary healthcare centres (PHCCs) staff in Indonesia. Design The NPC awareness programme consisted of 12 symposia including a Train-The-Trainer component, containing lectures about early symptoms and risk factors of NPC, practical examination and the referral system for NPC suspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Another aspect that may contribute to earlier presentation and diagnosis concerns raising awareness among healthcare professionals. A successful campaign was conducted in Indonesia in 2010–2011. The program consisted of two stages: firstly, GPs attended a series of seminars on nasopharyngeal cancer; and secondly, they were obliged to train their colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that may contribute to earlier presentation and diagnosis concerns raising awareness among healthcare professionals. A successful campaign was conducted in Indonesia in 2010–2011. The program consisted of two stages: firstly, GPs attended a series of seminars on nasopharyngeal cancer; and secondly, they were obliged to train their colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless in the long term, their knowledge consistently improved, suggesting that the program is effective for different health professions working in the PHCC. In addition they revealed that the nurses and midwives had less knowledge than general practitioners (GPs), but after the TrainÀTheÀTrainer program it was increased to more than the knowledge of the GPs, suggesting that different professions have different learning curves (Fles et al, 2016).…”
Section: High-risk Groupmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) is a malignancy that causes global health problems with 130,000 new cases and more than 70,000 deaths in 2018. 1 , 2 Unlike other neck and head malignancies, NPC is characterized by its ease of progress and metastasis. NPC has the highest tendency to metastasize to regional lymph nodes (LN).…”
Section: Introductionmentioning
confidence: 99%
“…It can maintain cell homeostasis through the formation of cadherin-catenin complexes. 6 Based on their distribution in tissues, the classic family of cadherins is divided into [1] E-cadherin was located in epithelial tissue; [2] N-cadherin in nerve tissue, muscle and fibroblasts; [3] P-cadherin was found in the placenta; [4] R-cadherin was found in the retina; and [5] M-cadherin in muscles. 7 N-cadherin consists of five intracellular domains.…”
Section: Introductionmentioning
confidence: 99%